Pengaruh Pemberian Pupuk Organik Cair (Kulit Pisang dan Air Cucian Beras) Terhadap Pertumbuhan dan Hasil Kacang Tanah (Arachis Hypogaea L.) - Putra, Yandi; Afrida; Prima Novia (Fakultas Pertanian, Universitas Ekasakti, 2022)
This research was conducted in Koto Panjang Ikur Koto Village, Koto Tangah District, Padang City with an altitude of 20 meters above sea level from March to June 2019. The aim of the study was to determine and obtain the best concentration of liquid organic fertilizer for banana peels and rice washing water for growth. and peanut yields. Experiments were carried out in the field using a randomized block design (RBD) with 6 treatments and 4 groups so that there were 24 experimental units in total. Each experimental unit consisted of 15 plants and 5 of them were sampled, totaling 360 plants, spacing 40 x 20 cm. The treatments given were various concentrations of POC banana peel and rice washing water as follows A: Without POC B: POC with a concentration of 4% C: POC with a concentration of 8% D: POC with a concentration of 12% E: POC with a concentration of 16% F: POC with a concentration of 20%. The data from the observations obtained were analyzed with the F test and continued with the Duncant's New Multiple Range Test (DNMRT). The results showed that the application of liquid organic fertilizer for banana peels and water washing rice to peanuts had no significant effect on plant height, number of primary branches, number of pods per plant, number of pithy pods per plant, weight of pods per plant, weight of pods per plot. , seed weight per plant, seed weight per plot and seed weight at 14% KA. The application of liquid organic fertilizer for banana peels and rice washing water has not been able to increase the growth and yield of peanut plants.